« Se mèt kò ki veye kò (chacun doit protéger farouchement son corps)»: représentations et thérapeutiques de la pandémie de Covid-19 en Haïti - Nadège Mézié; Obrillant Damus (Études Caribéennes)
The Covid-19 pandemic is reaching Haiti at a time the country has been in the throes of a serious political and social crisis, which has been going on since 2018. In this article, we show how there is widespread mistrust among the population not only in the government and the measures it has taken, but also against in biomedicine. This mistrust is characterized by counter-narratives that challenge the official political and biomedical public discourse. Secondly, we discuss how the disease has been classified and treated by Haitian Creole medicine with family or specialized practices of prevention and care using medicinal plants. In conclusion, we return to the expression, with strong political value, "se mèt kò ki veye kò".